The pattem of the conquest of the Polabian Slavs and Western Baltic lands from the point of view of Christianization of the Baltic tribes - Ščavinskas, Marius (Lietuvos istorijos studijos, 2010)
In the article there is the comparison of the pattern of the conquest of the Polabian tribes (including Polish Pomeranian areas) to that one of the Western Baltic tribes. Chronologically the conquest of the Polabian Slavic lands began already during the period of the first dynasty of Otton-Liudolfings (the first half of the 10th century), but the occupation itself, however, was over only in the middle of the 12th century. The lands of the Polabian Slavs were the target of occupation not only for the Saxons, but for Denmark and Poland as well (11th-12th centuries). Poland targeted all its energy towards the conquest of the Polish Pomeranian areas meanwhile Denmark, especially from the beginning of the 11th century, was trying to take hold of the Southern Seaside of the Baltic Sea. All these conquests had several important characteristics in common: 1) the establishment of the institutions of church and their incorporation into the church layers of the conquerors; 2) the implementation of the fiscal policy in the conquered lands; 3) the demand for the conquered tribes to observe the norms of Christian life, not separating this from the obedience to the conquerors.However, the nobility of the Polabian tribes (including Polish Pomeranian tribes) were yet granted some social, and what is most important, some political rights. It is true that historians are still arguing about what kind of structures they were and if there were any of them at all before the conquest began. One way or the other, it is evident, that the top of the nobility of the Polabian Slavs were granted certain political rights. These rights were determined by their vassal dependence on the Saxon earls, Polish dukes and Danish kings. However this right enabled separate ruling dynasties, which were entrusted the right of the fiscal policy, to be formed. Thus Pomeranian Dukes and the local Dukes of the Polabian Slavs became "their own" rulers towards their subordinates, if they had received the right of the Patronage in Church, became the donators of the monasteries. In this case, the political elite, while collaborating with the conquerors, were able to guarantee their minimal political and social rights.In the relationship to the Baltic tribes we can observe similar but yet different processes). Till the 12th century the Western Baltic tribes used to be the expansion target of the Polish Dukes and most often Danish kings. From the end of the 12th century the German elite of the Saxony and Polabian areas began to interfere between them. Since the foundation of the local military Orders of Knights didn’t yield good results, the Polish Dukes, related to the political elite of Saxony and Brandenburg, invited the German Order to come. The German Order took over the pattern of the conquest of the Polabian Slavic tribes (similarly to Saxons the German Order began to build the systems of castles in the conquered territories etc.). But at this point a distinct difference from the conquest of the Polabian Slavs appears. The nobility of the Western Baltic tribes (Prussian, Curonian, Semgallian and finally Ugric Livonian tribes in Livonia), contrary to the nobility of the Polabian tribes, were not granted any political rights. The establishment of the Church structures and the fiscal policy were kept in the hands of the German Order. The German Order enforced their laws on them as well. Thus, neither local political elite nor local dynasties were formed there. The local elite could expect just certain social concessions, which were limited after each uprising.In Prussia (as in Livonia) the German Order related the obedience to the adaptation of the norms of the Christian life to the local conditions. Loyal to the Order were considered only those, who not only observed the norms of the Christian life, as it had been agreed on in the Castle of Christburg and later put in the shape of certain laws, but those, who will loyally serve their conquerors and perform their duties. Of course, the military service to the conquerors could be performed only by the local elite, but it was forbidden to seek for the higher posts.Thus, the German/Livonian Order were executing the political and the social coercion in the conquered lands, meanwhile in the Polabian lands the social coercion towards their subordinates was executed by the local political elite, having received from the Saxons (from Poles in Pomeranian and from the Danish in the island of Rugen) the right to manage all local matters, including the ones related to the tax policy. The nobility of the Prussians, Livonians, Semgallians and Curonians were deprived of all this. In this aspect the conquest of Eastern Coast of the Baltic Sea was different from that one of Polabian Slavs and Pomeranian. In its turn the process of Christianization was influenced by that. This, by the way, is applicable to the process of Christianization of Lithuania, the efforts to prove this have already been made. However, in Lithuania there was the encounter with the state, not with the tribal society, and this aspect undoubtedly changes everything.
Keywords: -